Acute Kidney Injury in Mechanically Ventilated Patients: The Risk Factor Profile Depends on the Timing of Aki Onset. Issue 4 (October 2017) - Lombardi, Raúl; Nin, Nicolás; Peñuelas, Oscar; Ferreiro, Alejandro; Rios, Fernando; Marin, Maria Carmen; Raymondos, Konstantinos; Lorente, Jose A.; Koh, Younsuck; Hurtado, Javier; Gonzalez, Marco; Abroug, Fekri; et al.
ABSTRACT: Background: Acute kidney injury (AKI) is a frequent complication in patients under mechanical ventilation (MV). We aimed to assess the risk factors for AKI with particular emphasis on those potentially preventable. Study Design, Setting, and Participants: Retrospective analysis of a large, multinational database of MV patients with >24 h of MV and normal renal function at admission. AKI was defined according to creatinine-based KDIGO criteria. Risk factors were analyzed according to the time point at which AKI occurred: early (⩽48 h after ICU admission, AKIE ) and late (day 3 to day 7 of ICU stay, AKIL ). A conditional logistic regression model was used to identify variables independently associated with AKI. Results: Three thousand two hundred six patients were included. Seven hundred patients had AKI (22%), the majority of them AKIE (547/704). The risk factor profile was highly dependent upon the timing of AKI onset. In AKIE risk factors were older age; SAPS II score; postoperative and cardiac arrest as the reasons for MV; worse cardiovascular SOFA, pH, serum creatinine, and platelet count; higher level of peak pressure and Vt/kg; and fluid overload at admission. In contrast, AKIL was linked mostly to events that occurred after admission (lower platelet count and pH; ICU-acquired sepsis; and fluid overload). None ventilation-associated parameters were identify as risk factors for AKIL . Conclusions: In the first 48 h, risk factors are associated with the primary disease and the patient's condition at admission. Subsequently, emergent events like sepsis and organ dysfunction appear to be predictive factors making prevention a challenge. Abstract : Supplemental Digital Content is available in the text